Historic urban trees: Assessing the trunk’s internal integrity - Vieira-dos-Santos-Ataide, Glaycianne Christine; dos-Santos-Ataide, Danilo Henrique; Cerqueira-Martins, Bianca; Monteiro-de-Carvalho, Alexandre; de-Figueiredo-Latorraca, João Vicente (Bosque (Valdivia), 2023)
In addition to the general benefits that all trees provide, historic urban trees contribute significant cultural and affective value to the quality of life in cities. As these trees age, their maintenance requires meticulous and consistent attention to reduce associated risks. The objective of the present study was to identify and estimate the extent of internal damage in the trunk of historic urban trees. Forty-five Eucalyptus robusta trees located in a popular square in the city of Nova Friburgo-RJ, Brazil were evaluated. A visual analysis of the crown, trunk, and root system was performed, followed by complementary evaluations of acoustic tomography and, when necessary, resistography. Mathematical models were adjusted to infer the relationship and influence of dendrometric characteristics (total height, height to the first branch, diameter at 1.30 m above the ground, and crown diameter) and the mean resistographic amplitude on the mean wave propagation velocity acoustic. Most trees presented some form of external lesion on their trunks, and, generally, trees with severe lesions also exhibited alterations in the propagation velocity of acoustic waves and in the perforation resistance profile. The combination of different techniques allows for the identification of areas with possible internal injuries in the trunks of historic urban trees. However, it is worth noting that the extent of these areas varied among the techniques used.